PIBID/geography contributions to initial teacher training and challenging teaching challenges - Pinto, Louislane Araujo; Silva, Roberto Antero da; Mendes, Mauricio Ferreira (Revista Ensino de Geografia (Recife), 2020)
Experiences in classroom practice are essential for initial teacher education. This article aims to present contributions to the initial formation of teachers in Geography through experiences lived within the Institutional Program of Teaching Initiation Scholarship (PIBID) of the Federal University of Tocantins (UFT), Araguaína campus, referring to the period 2018 to 2019, guiding the cartographic education. . For this, we used case study techniques applied at Adolfo Bezerra de Menezes State College, located in Araguaína/TO as a learning laboratory and also a space for teacher training, associated with qualitative research, where the researcher works with the universe of phenomena. It is concluded that the PIBID is extremely important, since the program provides key elements in the articulation of several instructions in the teaching/learning process, in the application of new methodologies, providing an exchange of knowledge, guiding the theory/practice, obtaining positive results in the formation of teachers to act in Basic Education